PENGARUH CORPORATE GOVERNANCE PADA HUBUNGAN SUSTAINABILITY REPORT DAN REAKSI INVESTOR DI BURSA EFEK INDONESIA - I Gusti Ngurah Bagus Gunadi; I Gede Cahyadi Putra (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
Sustainability report is a report made by the company in order to disclose to all stakeholders regarding environmental, social and good governance performance. Sustainability reports are what companies need to provide information to investors about the company's sustainability. This study aims to analyze the effect of sustainability reports on investor reactions and the role of corporate governance on the relationship between sustainability reports and investor reactions. The research was conducted for 5 years with a sample of 6 mining companies from 48 mining companies on the Indonesia Stock Exchange. Sampling using purposive sampling method and data analysis techniques with moderated regression analysis. The results show that the sustainability report has a positive effect on investor reactions and corporate governance strengthens the relationship between sustainability reports and investor reactions.